A conceptual model of the data ecosystem formation in the health 4.0 - Mammadovа, Masuma; Ahmadova, Aytan Adil (OU Scientific Route, 2022)
Digitalization of health and medicine has become a global trend in recent years. The development of this trend is manifested in improving the quality of medical care, increasing access to medical services, and ensuring more effective health decisions. The global health trend is characterized by the transition from e-health to digital health, which is closely related to the formation and development of Industry 4.0. The projection of innovative approaches of Industry 4.0 into the health sector opens up great opportunities for creating a new healthcare paradigm (Health 4.0) by integrating modern technologies, analytical tools and smart medical devices. This article highlights Industry 4.0 technologies, the integration of which into healthcare has led to the generation of a huge amount of various data. Data collected through new technologies on the Health 4.0 platform, their types, structure, sources and capabilities are examined. It is shown that for the collection, transmission, storage, processing of heterogeneous data of a large volume, the introduction of new approaches and methods is required. In the environment of technological transformation, the evolution of the healthcare system at the data level and the conceptual model of the chain of formation of the Healthcare 4.0 ecosystem are proposed. The content of the components included in the Healthcare 4.0 data ecosystem is determined. Some problems arising in the formation of the data ecosystem on the Healthcare 4.0 platform and the processing of large health data are studied